Alteration in Taste Perception in Cancer: Causes and Strategies of Treatment - Murtaza, Babar; Hichami, Aziz; Khan, Amira S.; Ghiringhelli, François; Khan, Naim A. (Frontiers in Physiology, 2017)
The sense of taste is responsible for the detection and ingestion of food to cover energetic requirements in health and disease. The change in taste perception might lead to malnutrition that is usually one of the frequent causes of morbidity and mortality in patients with cancer. In this review, we summarize the mechanisms of taste perception and how they are altered in cancer. We also address the question of the implication of inflammation, responsible for the alterations in taste modalities. We highlight the role of radio- and chemotherapy in the modulation of taste physiology. Other several factors like damage to taste progenitor cells and disruption of gut microbiota are also dealt with relation to taste perception in cancer. We further shed light on how to restore taste acuity, by using different preventive methods, dietary modifications and pharmacotherapy in subjects with advanced cancer state.